Lung Adenocarcinoma Expressing an EML4‐ALK Fusion Transcript With Premature Stop Codons and Response to Alectinib: A Case Report. - Ozaki, Mami; Ikushima, Hiroaki; Suzuki, Masaki; Yokoyama, Akira; Fukuda, Kensuke; Watanabe, Kousuke; Shinozaki‐Ushiku, Aya; Kato, Motohiro; Ushiku, Tetsuo; Aburatani, Hiroyuki; Oda, Katsutoshi; Kage, Hidenori (Thoracic Cancer, 2025)
ALK fusions are well‐established oncogenic drivers in lung cancer, typically resulting in ALK activation through dimerization mediated by partner proteins. However, alternative mechanisms of ALK activation have also been reported. We herein report an 80‐year‐old man with metastatic lung adenocarcinoma, who initially tested negative for ALK rearrangement using a polymerase chain reaction‐based assay. RNA‐based hybrid capture targeted sequencing later identified an EML4‐ALK fusion transcript in which EML4 exon 15 and ALK intron 19 were fused. This resulted in a stop codon being retained in the unspliced ALK intron 19, preventing fusion protein translation. However, immunohistochemistry revealed overexpression of ALK, suggesting the existence of alternative translation initiation sites in exon 20 or downstream. The patient showed a marked response to alectinib therapy. This case underscores the importance of using multiple methods to detect actionable gene fusions and to ensure appropriate targeted therapy selection.